If the solve the problem

$\int \sin x \cos 2 x \sin 3 x d x$


We know $2 \sin A \cos B=\sin (A+B)+\sin (A-B)$

$\therefore \sin 3 x \cos 2 x=\frac{\sin 5 x+\sin x}{2}$

$\therefore$ The given equation becomes

$\Rightarrow \int \frac{1}{2}(\sin 5 x-\sin x) \sin x d x$

$\Rightarrow \int \frac{1}{2}\left(\sin 5 x \sin x d x-\sin ^{2} x d x\right)$

We know $2 \sin A \sin B=\cos (A-B)-\cos (A+B)$

$\therefore \sin 5 x \sin x=\frac{\cos 4 x-\cos 6 x}{2}$

Also $\sin ^{2} x=\frac{1-\cos 2 x}{2}$

$\therefore$ Above equation can be written as

$\Rightarrow \int \frac{1}{2}\left(\frac{1}{2}(\cos 4 x-\cos 6 x) d x-\frac{1}{2}(1-\cos 2 x) d x\right)$

$\Rightarrow \frac{1}{4} \int \cos 4 x d x-\int \cos 6 x d x-\int d x+\int \cos 2 x d x$

We know $\int \cos a x d x=\frac{1}{a} \sin a x+c$

$\Rightarrow \frac{1}{4}\left(\frac{1}{4} \sin 4 x-\frac{1}{6} \sin 6 x-x+\frac{1}{2} \sin 2 x+c\right)$

$\Rightarrow \frac{1}{4}\left(\frac{3 \sin 4 x-2 \sin 6 x-12+6 \sin 2 x}{12}+C\right)$

$\Rightarrow \frac{3 \sin 4 x-2 \sin 6 x-12+6 \sin 2 x}{48}+C$

NOTE: – Whenever you are solving integral questions having trigonometric functions in the product then the first thing that should be done is convert them in the form of addition or subtraction.


Leave a comment

Please enter comment.
Please enter your name.